Upregulation of an estrogen receptor-regulated gene by first generation progestins requires both the progesterone receptor and estrogen receptor alpha - Perkins, Meghan S.; Louw-du Toit, Renate; Jackson, Hayley; Simons, Mishkah; Africander, Donita (Frontiers in Endocrinology, 2022)
Progestins, synthetic compounds designed to mimic the activity of natural progesterone (P4), are used globally in menopausal hormone therapy. Although the older progestins medroxyprogesterone acetate (MPA) and norethisterone (NET) have been implicated in increased breast cancer risk, little is known regarding newer progestins, and no significant risk has been associated with P4. Considering that breast cancer is the leading cause of mortality in women, establishing which progestins increase breast cancer incidence and elucidating the underlying mechanisms is a global priority. We showed for the first time that the newer-generation progestin drospirenone (DRSP) is the least potent progestin in terms of proliferation of the estrogen-responsive MCF-7 BUS breast cancer cell line, while NET and P4 have similar potencies to estradiol (E2), the known driver of breast cancer cell proliferation. Notably, MPA, the progestin most frequently associated with increased breast cancer risk, was significantly more potent than E2. While all the progestogens enhanced the anchorage-independent growth of the MCF-7 BUS cell line, MPA promoted a greater number of colonies than P4, NET or DRSP. None of the progestogens inhibited E2-induced proliferation and anchorage-independent growth. We also showed that under non-estrogenic conditions MPA and NET, unlike P4 and DRSP, increased the expression of the estrogen receptor (ER) target gene, cathepsin D, via a mechanism requiring the co-recruitment of ERα and the progesterone receptor (PR) to the promoter region. In contrast, all progestogens promoted the association of the PR and ERα on the promoter of the PR target gene, MYC, thereby increasing its expression under non-estrogenic and estrogenic conditions. These results suggest that progestins differentially regulate the way the PR and ER converge to modulate the expression of PR and ER-regulated genes. Our novel findings indicating similarities and differences between P4 and the progestins, emphasize the importance of comparatively investigating effects of individual progestins rather than grouping them as a class. Further studies are required to underpin the clinical relevance of PR/ERα crosstalk in response to different progestins in both normal and malignant breast tissue, to either confirm or refute their suitability in combination therapy for ER-positive breast cancer.